-
1)(3x+1)^2=7
Solution: (3x+1) 2=7 (3x+1) 2=7 3x+1= 7 (be careful not to lose the solution) x= ( 7-1) 3
2)9x^2-24x+16=11
Solution: 9x 2-24x+16=11 (3x-4) 2=11 3x-4= 11 x= ( 11+4) 3 The solution of the original equation is x1=( 11+4) 3 x2=(- 11+4) 3
3) (x+3)(x-6)=-8
Solution: (x+3)(x-6)=-8 Simplified x 2-3x-10=0 (the left side of the equation is a quadratic trinomial, and the right side is zero) (x-5)(x+2)=0 (the left side of the equation is factored) x-5=0 or x+2=0 (converted into two unary linear equations) x1=5, x2=-2 is the solution of the original equation.
4) 2x^2+3x=0
Solution: 2x 2+3x=0 x(2x+3)=0 (factor the left side of the equation by the common factor method) x=0 or 2x+3=0 (convert into two unary equations) x1=0, x2=-3 2 is the solution of the original equation. Note:
Some students tend to lose the solution of x=0 when doing this kind of problem, and should remember that there are two solutions to a quadratic equation.
5) 6x 2+5x-50=0 (elective).
Solution: 6x2+5x-50=0 (2x-5)(3x+10)=0 (pay special attention to the symbols when factoring the cross multiplication) 2x-5=0 or 3x+10=0 x1=5 2, x2=-10 3 is the solution of the original equation.
6) x 2-4x+4=0 (elective).
Solution: x 2-4x+4 =0 ( 4 can be decomposed into 2 ·2 , this problem can be factored by factoring) (x-2) (x-2 )=0 x1=2 , x2=2 is the solution of the original equation.
7)(x-2)^2=4(2x+3)^2
Untie. (x-2)^2-4(2x+3)^2=0. [x-2+2(2x+3)][x-2-2(2x+3)=0.
5x+4)(-5x-8)=0.
x1=-4/5, x2=-8/5
8)y^2+2√2y-4=0
Solution(y+2) 2-2-4=0
y+ √2)^2=6.
y+√2=√6.
y=-√2±√6.
y1=-√2+√6;
y2=-√2-√6.
9)(x+1)^2-3(x+1)+2=0
solution (x+1-1)(x+1-2)=0.
x(x-1)=0.
x1=0,x2=1.
10) x 2+2ax-3a 2=0 (a is constant).
solution (x+3a)(x-a)=0.
x1=-3a,x2=a.
-
From the meaning of the title, a2+3a+1=0 can be converted into a2(a2+3a+1)-2a(a2+3a+1)-(a2+3a+1)+6=6
-
.(x+2) 2=16 x+2=+-4 x=-6 and x=22 3x 2-2x-1=0 (3x+1)x(x-1)=0 x=-1 3 x=1
The rest is counted with a universal formula! When b 2-4ac>=0, the equation has a solution so x=[-b+sqrt(b 2-4ac)] 2a
The other x=[-b-sqrt(b 2-4ac)] 2a, where b 2-4ac is under the root number! That is, sqrt lookout.
-
/2(x+2)ˆ2-8=0
1/2(x+2)ˆ2=8
x+2)ˆ2=16
x+2=+4 or -4
x = 2 or -6
Count yourself for something similar.
-
Such a simple question can be calculated by yourself. /
-
8: Set: The original amount of coal is x?
x-15)÷(15÷3×1/2)+3-10=x÷(15÷3)(x-15)×2/5-7=x/5
2x/5-6-7=x/5
x/5=13
x 6510: Tree planting this year x(1 20)11: Which of the following statements is incorrect: c
14: The two-digit numbers are: b and c
20: The ** price needs to be a9% off. (1 8 ) 1 20 ) 23: Set: Apple bought x kilograms?
4x+(5-x)×3=17
4x+15-3x=17
x 2 pears 5 2 3 kg.
This is relatively simple, for example: x=8, y=9, these are all unary equations.
1.A two-digit number, the number on the municipal party committee is twice the number on the one digit, if the number on the ten digit is reversed with the number on the person, then the number obtained is 36 smaller than the original, find the original number. >>>More
2x 10 1=7 2x=7-1 2x=6 x=6 2 x=3 You just give me the title and I'll write it all for you?
1. Solution: 1) Set up a total of x potted flowers purchased by the school, and the number of flowers assigned to each class is equal. >>>More
Solve the following unary equations.